RADIOGRAPHIC EXAMINATION TECHNIQUES OF LUMBAL VERTEBRA IN CASE OF LOW BACK PAIN IN ISLAMIC HOSPITAL PURWOKERTO - Fitriana Fitriana; Hernastiti Sedya Utami; Festyana Filauhid (Medical Imaging and Radiation Protection Research Journal, 2022)
Low Back Pain (LBP) is a pain condition that attacks the lower part of the spine, caused by injury to muscles or ligaments, common causes include lifting the wrong weight, poor posture, not exercising regularly and so on. One of the radiological examinations to establish the diagnosis of LBP is a radiographic examination of the lumbar spine. In the examination procedure, the radiological examination of the lumbar spine, the patient's position during the examination was arranged to sleep supine on the examination table, while at RSI Purwokerto the examination of the lumbar vertebrae with the case of LBP the patient position setting was arranged to stand in front of the bucky stand. The research used in the preparation of this scientific article is qualitative research with approach case study, the method of data collection is carried out by direct observation of the technique of radiographic examination of the lumbar spine with LBP cases at the Radiology Installation of Islamic Hospital Purwokerto and data collection methods by taking data from documents, including radiographs, medical records and radiographic readings. On radiographic examination of the lumbar spine with LBP cases with the patient standing, the results were: low back pain with normal lumbar curvature and no disc narrowing. Conclusions that can be drawn from the technique of examining the lumbar vertebrae at the Radiology Installation of the Islamic Hospital of Purwokerto were carried out with the AP and Lateral erect projections. the use of this projection can be more informative and can clarify the intervertebral space or narrowed intervertebral disc.